2023
DOI: 10.1172/jci.insight.167903
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid enhancement of lncRNA MMP25-AS1/MMP25 interaction reduces neutrophil infiltration and intestinal epithelial injury in HIV/SIV infection

Abstract: Intestinal epithelial barrier dysfunction, a hallmark of HIV/SIV infection, persists despite viral suppression by combination antiretroviral therapy (cART). Emerging evidence suggests a critical role for long noncoding RNAs (lncRNAs) in maintaining epithelial homeostasis. We simultaneously profiled lncRNA/mRNA expression exclusively in colonic epithelium (CE) of SIV-infected rhesus macaques (RMs) administered vehicle (VEH) or Δ-9-tetrahydrocannabinol (THC). Relative to controls, fewer lncRNAs were up- or downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Emerging evidence suggests the involvement of epigenetic mechanisms, particularly long non-coding RNAs (lncRNAs), in maintaining epithelial homeostasis. Premadasa et al [64] recently showed that THC enhanced the interaction between long non-coding RNA MMP25-AS1 and its associated protein coding gene MMP25. Enhancement of this interaction was associated with reduced neutrophil transendothelial/transepithelial migration in the colon in chronic HIV/SIV infection.…”
Section: Cannabis Hiv and Gut-brain Axismentioning
confidence: 99%
“…Emerging evidence suggests the involvement of epigenetic mechanisms, particularly long non-coding RNAs (lncRNAs), in maintaining epithelial homeostasis. Premadasa et al [64] recently showed that THC enhanced the interaction between long non-coding RNA MMP25-AS1 and its associated protein coding gene MMP25. Enhancement of this interaction was associated with reduced neutrophil transendothelial/transepithelial migration in the colon in chronic HIV/SIV infection.…”
Section: Cannabis Hiv and Gut-brain Axismentioning
confidence: 99%